Effect of Benzene on Some haeMatological Parameters of Oil Station Workers - Hameed, F. R.; Alhusein, A.Abd-; Salim, A.; Hussein, M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Benzene is a hydrocarbon chemical consisting of six atoms arranged in a ring structure. At normal ambient temperatures; it is a liquid, which evaporates rapidly at room temperature and is highly flammable. It has a characteristic of aromatic odor and is slightly soluble in water (1.5 g/liter at 20ÂºC) but miscible with most other organic solvents [1].           Long-term inhalation of benzene causes blood disorders. It specifically affects bone marrow [2]. And it may cause anemia, excessive bleeding, damage to the immune system and DNA [3, 4]. Increased incidence of leukemia (cancer of the tissues that form white blood cells) has been observed in people occupationally exposed to benzene; so (EPA) Environmental Protection Agency has classified benzene as a known human carcinogen [5].     The present study was conducted to evaluate the effect of benzene on some hematological parameters on 60 males working in different oil stations that provide benzene products for people at Waset governorate with a mean year for work duration 1 to 20 years, 8 hours of work as a mean per day.       A haemoglobin (Hb) concentrations as well as white blood cells count (W.B.Cs) and platelets count (Plt) were well observed to evaluate the effect of benzene on these parameters. Results showed that workers in oil stations indicated normal values for haemoglobin 13.2 and white blood cells (5640 cell/cmm) and platelets 261000 during the first 10 years of work.     As the duration of work progresses, results indicated that there was a gradually reduction in all parameters.